2004
DOI: 10.1002/cne.11016
|View full text |Cite
|
Sign up to set email alerts
|

Bromodeoxyuridine administered during neurogenesis of the projection neurons causes cerebellar defects in rat

Abstract: Bromodeoxyuridine (BrdU) is broadly used in neuroscience to study embryonic development and adult neurogenesis. The potential toxicity of this halogenated pyrimidine analogue is frequently neglected. In this study, we administered BrdU in small doses by the progressively delayed cumulative labeling method to immunocytochemically tag different cerebellar cell types with antibodies to specific markers and BrdU in the same section. The well-known structure of the cerebellum made it possible to ascertain several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 82 publications
1
50
0
2
Order By: Relevance
“…Together with previous birthdating studies (Altman and Bayer, 1997;Sekerková et al, 2004a;Yamanaka et al, 2004), our present analyses indicate that cerebellar GABAergic interneurons are generated between E13 and P15. Within this time window, the different phenotypes are produced during overlapping periods, according to an inside-out sequence: first in the deep nuclei, then in the granular layer, and, finally, in the molecular layer.…”
Section: Localization Of Interneuron Progenitors In the Postnatal Cersupporting
confidence: 88%
See 1 more Smart Citation
“…Together with previous birthdating studies (Altman and Bayer, 1997;Sekerková et al, 2004a;Yamanaka et al, 2004), our present analyses indicate that cerebellar GABAergic interneurons are generated between E13 and P15. Within this time window, the different phenotypes are produced during overlapping periods, according to an inside-out sequence: first in the deep nuclei, then in the granular layer, and, finally, in the molecular layer.…”
Section: Localization Of Interneuron Progenitors In the Postnatal Cersupporting
confidence: 88%
“…Although birthdating studies indicate that all nuclear neurons are generated at the beginning of cerebellar neurogenesis [i.e., between E13 and E15 in the rat Bayer, 1978, 1997;Sekerková et al, 2004a)], other reports suggest that local inter- 9c 14 0 0 0 14 7c 62 0 0 0 62 10c 525 1 0 0 526 2c 492 3 0 0 495 11c 299 0 0 1 300 3c 513 0 0 0 513 1c 279 0 0 0 279 6c 417 0 0 0 417 4c 439 0 0 0 439 5c 101 0 0 0 101 8c 582 0 0 0 582 tot 2239 1 0 1 2241 tot 1484 3 0 0 neurons have a different origin than projection neurons (Hoshino et al, 2005;Wang et al, 2005;Fink et al, 2006) and may be also generated at later stages (Maricich and Herrup, 1999). Therefore, as a preliminary step for our study, we reexamined deep nuclei neurogenesis to define the time window in which local interneurons are born.…”
Section: Resultsmentioning
confidence: 99%
“…A higher dose was thus employed to maximize the amount of label at long survival times. Although BrdU has toxic and mutagenic effects when administered to pregnant or developing mammals [Kolb et al, 1999;Sekerková et al, 2004], no such effects have been observed in adult mammals administered doses as high as 600 mg/kg [Cameron and McKay, 2001]. We observed no obvious toxic effects of or behavioral abnormalities resulting from the high doses of BrdU administered to our ex-perimental animals.…”
Section: Brdu Immunohistochemistrymentioning
confidence: 58%
“…Some animals received a single BrdU injection of 200 g/gm body weight. This dose of BrdU is reported to more completely label DNA synthesizing cells in situ (Cameron and McKay, 2001), although high concentrations of BrdU have been reported to be toxic (Sekerkova et al, 2004). Using this protocol, we again obtained no apparent difference in the number of BrdU ϩ cells between WT and Bax-KO mice (3150 cells in WT mice, and 2870 cells in Bax-KO mice; n ϭ 1 in each group).…”
Section: Production Of New Cells In the Adult Dg Is Not Modified Aftementioning
confidence: 58%